2023
DOI: 10.1186/s12913-023-09263-4
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness and budget impact of heat-stable carbetocin compared to oxytocin and misoprostol for the prevention of postpartum hemorrhage (PPH) in women giving birth in India

Abstract: Introduction Low- and middle-income countries (LMICs) are committed to achieving the Sustainable Development Goal 3.1 to reduce maternal mortality. The Ministry of Health and Family Welfare of India recommends prophylactic uterotonic administration to every woman following delivery to reduce the risk of postpartum hemorrhage (PPH), as PPH is the leading cause of maternal mortality in LMICs, including India. In 2018, the World Health Organization first recognized heat-stable carbetocin for PPH p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In terms of health economic evidence, a network meta-analysis and systematic review found the relative cost-effectiveness of heat-stable carbetocin compared to alternative strategies to be inconclusive due to the uncertainty and inconsistency in the data reported on adverse events [37,38]. Yet some recent studies in LMICs have shown that heat-stable carbetocin can be a cost-effective alternative to oxytocin [39][40][41]. The manufacturer of heat-stable carbetocin has made a commitment to increase its availability to primary health care facilities in LMICs at an affordable price [35].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…In terms of health economic evidence, a network meta-analysis and systematic review found the relative cost-effectiveness of heat-stable carbetocin compared to alternative strategies to be inconclusive due to the uncertainty and inconsistency in the data reported on adverse events [37,38]. Yet some recent studies in LMICs have shown that heat-stable carbetocin can be a cost-effective alternative to oxytocin [39][40][41]. The manufacturer of heat-stable carbetocin has made a commitment to increase its availability to primary health care facilities in LMICs at an affordable price [35].…”
Section: Plos Global Public Healthmentioning
confidence: 99%